2009
DOI: 10.1007/s10571-009-9469-0
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Alters Aromatase Enzyme Levels in Sciatic Nerve and Hippocampus Tissues of Rats

Abstract: Diabetes mellitus (DM) is associated with increased risk of impaired cognitive function. Diabetic neuropathy is one of the most common and important complications of DM. Estrogens prevent neuronal loss in experimental models of neurodegeneration and accelerate nerve regeneration. Aromatase catalyzes the conversion of androgens to estrogens and expressed in a variety of tissues including neurons. Although insulin is known to regulate the activity of aromatase there is no study about the effects of diabetes on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The results support that the neuronal protective effects of estrogen may also play an important role in the female individuals who showed fewer cognitive deficits than males. This finding is also supported by a series of other studies [41][42][43][50][51][52]. However, some studies have failed to find that estrogen has significant protective effects for cognitive function in females rather than males with diabetes only [29,33].…”
Section: Accepted M Manuscriptsupporting
confidence: 61%
See 1 more Smart Citation
“…The results support that the neuronal protective effects of estrogen may also play an important role in the female individuals who showed fewer cognitive deficits than males. This finding is also supported by a series of other studies [41][42][43][50][51][52]. However, some studies have failed to find that estrogen has significant protective effects for cognitive function in females rather than males with diabetes only [29,33].…”
Section: Accepted M Manuscriptsupporting
confidence: 61%
“…Several studies have indicated that poorer glycemic control and higher HbA1c are significantly associated with cognitive deficits [21,23,[41][42][43][44][45]. Studies have also shown that female individuals with diabetes have poorer glycemic control and a higher HbA1c concentration than males [24].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…For instance, the expression of aromatase is altered by long-term diabetes in a sex specific way. Indeed, the expression of this enzyme is increased in the sciatic nerve of female but not of male rats (Burul-Bozkurt et al, 2010).…”
Section: Peripheral Neuropathymentioning
confidence: 93%
“…This results in the conversion of testosterone and androstenedione to estradiol and estrone, respectively, which contribute to reducing serum testosterone concentrations in men with diabetes (42)(43)(44)(45)(46)(47). In addition, the disruption of glucolipid metabolism, the reduced bioavailability of insulin during diabetes and the reduced activity of CYP19 in the ovaries of diabetic rats, as determined by Bozkurt et al, might be responsible for the reduced levels of estradiol in females with diabetes (48)(49)(50).…”
Section: Alterations In Sex Hormones In Diabetesmentioning
confidence: 96%